Optimizing resource use efficiency for sustainable paddy production in South India - a regional study - Felix, K. Thomas; Govindarajan, Padma Lakshmi; Rashtrarakshak, V. P. (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe inefficient use of inputs in paddy production leads to either over-exploitation or under-exploitation of natural resources, thereby minimizing productivity and sustainability. This study investigates Resource Use Efficiency (RUE) in paddy production across South Indian states.MethodsThe study uses secondary data extracted from the Directorate of Economics and Statistics, Department of Agriculture and Farmers’ Welfare, Ministry of Agriculture and Farmers Welfare, Government of India for the period 2022-23 for the South Indian states – Andhra Pradesh, Karnataka, Kerala, Tamil Nadu and Telangana. The research employed Cobb–Douglas production function analysis and RUE estimation to compare the RUE among the study states using the variables like paddy yield, labor (human, animal and machine), fertilizer usage, irrigation and seed application.Results and DiscussionThe key findings revealed significant regional disparities in paddy productivity and input efficiency. Telangana has emerged as the most productive state with efficient input–output relationships, whereas Kerala lagged in productivity despite its high input usage. The analysis identifies widespread underutilization of critical inputs, including fertilizers, seeds, and irrigation, across most states, in contrast to the excessive use of labor resources. State-specific interventions for enhancing paddy productivity include optimizing labor and seed rate efficiency in Kerala, fertilizer use efficiency in Tamil Nadu, and capital use (mechanization) efficiency in Andhra Pradesh. The quantitative analysis results reveal the inefficient use of inputs and overuse of labor resources across the states.Policy SuggestionsThe implementation of targeted, region-specific, and state-specific strategies, including investments in irrigation infrastructure, promotion of balanced application of fertilizers, adoption of good quality and high-yielding varieties of seeds, and increase in technology adoption, will optimize the input use and enhance the paddy productivity in South India.